THE CONFLICTS IN SHAKESPEARE’S DRAMA HAMLET - Syamsul Bahri (BAHAS, 2015)
This study explores several conflicts found in the literary work of Shakespeare’s Drama Hamlet. It uses an intrinsic approach in which there are some explanations and elaborations about the different conflicts those can be categorized in internal and external. Internal conflict happens on Hamlet’s when the spirit of his father comes and asks  him to do a revenge on the death of his father murdured by his uncle, Claudius. On the other hand, Ophelia is also mentally struck by a huge burden on the death of his father unpurposely killed by Hamlet. It really disturbs her mind, mental and makes her become mad and finally she is dead in a suffer.  Several external conflicts are also found in Hamlet. The conflict happenes between individual to another individual. It is found that Hamlet has a great anger to Claudius and wants to kill him because Claudius murdures his father and marries his mother. In the match of sword with Laertes, Hamlet has a chance to kill Claudius. External conflict also happens between Hamlet and his mother, Getrude. Hamlet supposes his mother has his father much offended, and almost as bad as a King, Claudius who murdures his father. The strange conduct on Hamlet makes Getrude anxious and it raises a conflict with her son. The Other external conflict is also found between Hamlet and Laertes. Laertes has a great anger with Hamlet on the death of his father killed unpurposely by Hamlet. In the match of sword, both of them are finally dead. The moral values can be attained in the play of Hamlet that a revenge is not a good one because it can rise a suffer to someone  or himself and bring   into the death. The greediness of wealth and  power can rise a great problem and hurt himself or other people. Kata Kunci : The Conflicts, Drama, Hamlet